Free Communications of the Gulf Association of Endocrinology and Diabetes Clinical Congress, October 18–20, 2024, Abu Dhabi, United Arab Emirates - Hussein, Wiam I.; Alessa, Thamer; Alrisi, Ali; Afandi, Bachar; Almazrouei, Raya; Aljohani, Naji (Journal of Diabetes and Endocrine Practice, 2025)
These are the abstracts of the Clinical Congress of the Gulf Association of Endocrinology and Diabetes (GAED) held on October 18 to 20, 2024. The program included plenary lectures and clinical practice symposia delivered by international and regional key opinion leaders. In addition, free communications on current research and clinical practice within and beyond the Gulf region were presented as oral presentations and posters. We present here the abstracts of these free communications after minimal restyling and editing to suit the journal’s publication requirements. We hope that by publishing them in our open-access journal, we provide early recognition of the work and extend the benefit to those who could not make it to the live presentations, similar to our previous conferences. We also hope to stimulate networking between parties of mutual research interests.
Keywords: diabetes; endocrinology; cardiometabolic; education; research; professionalism; diabetes technology